Floral evidence for high summer temperatures in southern Scandinavia during 15–11 cal ka BP. (1st April 2020) - Schenk, Frederik; Bennike, Ole; Väliranta, Minna; Avery, Rachael; Björck, Svante; Wohlfarth, Barbara
Abstract: The global climate transition from the Lateglacial to the Early Holocene is dominated by a rapid warming trend driven by an increase in orbital summer insolation over high northern latitudes and related feedbacks. The warming trend was interrupted by several abrupt shifts between colder (stadial) and warmer (interstadial) climate states following instabilities of the Atlantic Meridional Overturning Circulation (AMOC) in response to rapidly melting ice sheets. The sequence of abrupt shifts between extreme climate states had profound impacts on ecosystems which make it challenging to reliably quantify state variables like July temperatures within a non-analogue climate envelope. For Europe, there is increasing albeit inconclusive evidence for higher stadial summer temperatures than initially thought. Here we present a comprehensive floral compilation of plant macrofossils from lake sediment cores of 15 sites from S-Scandinavia covering the period ∼15 to 11 ka BP. We find evidence for a continued presence of plant species indicating high July temperatures throughout the last deglaciation. The presence of hemiboreal plants in close vicinity to the southern margin of the Fennoscandian Ice Sheet implies a strong thermal summer forcing for the rapid ice sheet melt. Consistent with some recent studies, we do not find evidence for a general stadial summer cooling, which indicates that other reasons than summer temperatures caused drastic setbacks in proxy signals possibly driven by extreme winter cooling and/or shorter warm seasons. Highlights: Common northern distribution limits of climate indicator plant species are used to reconstruct past summer temperatures. Indicator plants suggest surprisingly high July temperatures throughout the Lateglacial in S-Scandinavia. Presence of cold-adapted plants points towards long severe winters and hence a continental climate with strong seasonality.